Internal and external subjects of financial control over the reliability of financial statements - E. A. Naumova (Путеводитель предпринимателя)
The article substantiates the relevance of research into issues of increasing the reliability of financial reporting. In this regard, the formation of an effective system of financial control over accounting reporting is identified as a primary task. To solve this problem, it is necessary to increase the efficiency of control both in the process of generating reports and subsequent control over already compiled reports. Internal control is provided directly by the accounting service and independent internal controllers, including an internal controller, auditor, and auditor. External control is provided by tax services in the process of forming the state information resource of accounting financial statements and audit companies. The article examines the functions of the main elements of the financial control system for accounting reports and suggests directions for improving the efficiency of their activities. Particular attention is paid to internal control and external audit systems, the functioning of which should be aimed at increasing the reliability of financial reporting in the interests of external users.